Charting the future of library and information science in Australia and New Zealand through research, education and practice partnerships - Edward Luca; Bhuva Narayan; Mary Anne Kennan (Information Research: An International Electronic Journal)
Introduction. This paper reports on a year-long research project examining the state of library and information science (LIS) in Australia and New Zealand (ANZ), where there is a decreasing number of LIS programmes and ensuing concerns around the future of LIS education, and hence LIS research and LIS practice.